The architect's studio companion : rules of thumb for preliminary design - Allen, Edward, 1938-; Iano, Joseph (Hoboken, NJ : Wiley, 2017)
'The Architect's Studio Companion is the only handbook the practicing architect needs. Packed with useful information, it is more than simply a reference'--
Includes bibliographical references and index.
Keywords: Architectural design -- Handbooks, manuals, etc